From "Leader" to "Soul-Caster": The Awakening and Reshaping of Principals’ Research and Study Leadership ——A In-Depth Documentary and Reflection on the "Golden Seed" Training Program for Principals’ Research and Study Leadership Improvement in Heilongjiang Province - Min Zeng; Bin Yu (Education Research on Study Tours and Practice, 2026)
Against the backdrop of the strategy of building a powerful country in education and the comprehensive revitalization of Heilongjiang Province, research and study practice education has been entrusted with a new mission of fostering virtue and cultivating people. Taking the first training program for the improvement of principals’ research and study leadership under the "Golden Seed" Initiative in Heilongjiang Province as the research subject, this paper analyzes its innovative training model of policy anchoring + practical immersion + achievement transformation. Combined with detailed media coverage data and authentic experience shared by participating principals, it explores how principals’ research and study leadership evolves from administrative imperative to professional self-awareness.The paper points out that "Golden Seed" is not merely a code name for a training program, but also the inheritance of educational feelings and the reshaping of educational governance capacity. It has formed a replicable Heilongjiang Model for the high-quality development of regional research and study practice, and provided theoretical reference and practical paradigm for the innovation of principal training models in the new era.